Anatomy-guided resections for paralimbic tumors in the temporo-insular region: combining tumor and epilepsy surgery concepts - Alkassm, Emad; Grote, Alexander; Berger, Björn; Woermann, Friedrich G.; Ersoy, Tunc Faik; Coras, Roland; Kalbhenn, Thilo; Simon, Matthias (Frontiers in Neurology, 2024)
Object: Tumors of the temporo-mesial region often extend into the insula and vice versa. The present study investigated the results of a surgical strategy that combines tumor as well as epilepsy surgery principles.We retrospectively studied 157 consecutive patients with intrinsic brain tumors growing in the temporo-mesial region with variable extensions into the insula (44 [28.0%]).The surgical strategy addressed anatomical compartments ("anatomy guided resection") defined by specific surgical maneuvers necessary for resecting the respective tumor infiltration (e.g. temporal pole, anterior temporo-mesial = uncus and hippocampal head, posterior temporomesial, insula etc.) rather than a single tumor mass.Results: Ganglioglioma CNS WHO grade 1 (55 [35.0%]) and (IDH 1 wildtype) glioblastoma (36 [22.9%]) were the two most frequent histologies encountered. The majority of cases was found to have tumor infiltration of the anterior temporo-mesial compartment (145 [92.4%]). In overall 131 cases (83.4%) an anterior temporal lobectomy was at least part of the surgical concept. All seventy-six (48.4%) patients presenting with drug resistant epilepsy underwent a formal presurgical epilepsy work-up (including placement of depth electrodes: 3). One hundred and seventeen cases (74.5%) had a complete resection including 89 patients (56.7%) with supramarginal resections. Four patients incurred non-temporary neurological Common Terminology Criteria for Adverse Events (CTCAE) grade 3-5 complications. On hundred and twenty-seven of 147 assessable patients (86.4%) reported no seizures or auras (International League against Epilepsy, ILAE class 1) at 6 months (excluding early/ <30 days postoperative seizures). 122 (84.7%) of 144 assessable cases had ILAE class 1 outcomes at 24 months. Kaplan Meier estimates for 5-year overall survival were 98.5% for non-recurrent glioneuronal tumors, and the 2-year overall survival estimates were 96.0% for 24 primary diffuse CNS WHO grade 2 and 3 gliomas, and 55.2% following 30 first surgeries for glioblastomas/astrocytomas CNS WHO grade 4.Combining epilepsy and tumor surgery concepts for the surgical treatment of intrinsic brain tumors involving the mesial temporal lobe and often extending into the insula resulted in more extensive resections, improved seizure outcomes and potentially even better patient survival.